PENGARUH KARAKTERISTIK PEKERJAAN DAN KONFLIK WORK-FAMILY TERHADAP KEPUASAN KERJA DENGAN DIMEDIASI KOMITMEN ORGANISASIONAL (Studi pada Lingkungan Kantor Pelayanan Pajak Pratama Semarang Candisari dan Kantor Pelayanan Pajak Pratama Semarang Tengah Satu) (Students' Journal of Economic and Management, 2013)
Work of family conflict often occurs in people's lives in general. Selection of characteristics relevant to their work and expertise of employees is an issue that can not be ignored in the psychological field of industry. Problems were also experienced by the tax officials who are in KPP Pratama Semarang Candisari and KPP Pratama Semarang Tengah Satu totaling 108 respondents that affect the job satisfaction of employees. Organizational commitment can grow when expectations can be met by organizations working properly, then the work will lead to unfulfilled expectations of job satisfaction (Setyawan, 2008). The test results are partially positive influence between job characteristics on organizational commitment, then there is a partial negative influence between the work of family conflict on organizational commitment, there is a partial positive influence between job characteristics on job satisfaction, there is a partial negative influence between work of family conflict on job satisfaction, and there is a partial positive influence between organizational commitment on job satisfaction. The results showed that the mediation that organizational commitment mediates the effect of job characteristics on job satisfaction and organizational commitment mediates the effect of work-family conflict on job satisfaction. Keywords:    Job characteristics, Work of family conflict, Organizational commitment and Job satisfaction